The Effects of Different Oil Sources on Performance, Digestive Enzymes, Carcass Traits, Biochemical, Immunological, Antioxidant, and Morphometric Responses of Broiler Chicks - Attia, Youssef A.; Al-Harthi, Mohammed A.; Abo El-Maaty, Hayam M. (Frontiers in Veterinary Science, 2020)
This research evaluate the influence of different oil sources, namely fish oil (FO), coconut oil (CocO), canola oil (CanO), or a mixture of the three oils (MTO)—included at 1.5% in broiler diets—compared to a no oil-supplemented diet. Hence, 250 unsexed, 1-day-old Cobb chicks were weighed and randomly allocated into five dietary treatment groups of 50 chicks each and five replicates per group. Oil-supplemented diets significantly increased the growth, improved the feed conversion ratio (FCR), and decreased the abdominal fat percentage compared to the control diet. Amylase was significantly elevated due to feeding the FO- or CocO-supplemented-diet compared to the control diet, whereas lipase increased due to offering CocO- and CanO-enriched diet; chymotrypsin increased due to different oil sources. High-density lipoprotein cholesterol (HDL-C) increased markedly due to offering an oil-supplemented diet, but low-density lipoprotein cholesterol (LDL-C), the LDL-C:HDL-C ratio, and malondialdehyde (MDA) decreased. Blood plasma immunoglobulin (Ig) G and IgM significantly increased due to feeding CocO, CanO, or MTO compared to the control group, whereas FO increased IgG only. FO- and CanO-containing diets resulted in the highest increase in α2-globulin and γ-globulin. The antibody titer to avian influenza (HIAI) and Newcastle disease (HIND) were significantly elevated due to CocO supplementation compared to the control group. The bursa follicle length and width and thymus cortex depth were increased considerably due to the FO-supplemented diet compared to the control, but the follicle length:width ratio decreased. The villus height:depth ratio was significantly elevated due to both the CanO and MTO diets. The antioxidant status improved considerably due to the addition of CocO and CanO. Both CanO and MTO similarly increased plasma T3, T4, and the T3:T4 ratio. The FO significantly increased meat’s omega-3 fatty acids compared to the control, while CanO significantly increased polyunsaturated fatty acids (PUFA). In conclusion, these oils enhanced growth performance and immune status, improved the blood lipid profile and antioxidants status and the health index of broiler meat, denoted by a significant decrease in the atherogenic and thrombogenic indexes and an increase in the meat’s cholesterol-lowering effect, and the effect of the oil sources depends on criteria of response.